Understanding syntax - Tallerman, Maggie, 1957- (Understanding language series, 2020)
"Assuming no prior grammatical knowledge, Understanding Syntax explains and illustrates the major concepts, categories and terminology involved in the study of cross-linguistic syntax. Taking a theory-neutral and descriptive viewpoint throughout, this book: introduces syntactic typology, syntactic description and the major typological categories found in the languages of the world; clarifies with examples grammatical constructions and relationships between words in a clause, including word classes and their syntactic properties; grammatical relations such as subject and object; case and agreement processes; passives; questions and relative clauses; features in-text and chapter-end exercises to extend the reader's knowledge of syntactic concepts and argumentation, drawing on data from over 100 languages; highlights the principles involved in writing a brief syntactic sketch of language. This fifth edition has been revised and updated to include extended exercises in all chapters, updated further readings, and more extensive checklists for students. Accompanying e-resources have also been updated to include hints for instructors and additional links to further reading. Understanding Syntax is indispensable for students studying the description of language, cross-linguistic syntax, language typology, and linguistic fieldwork"--